Frequency of pregnant women with HBsAg in a Brazilian community Freqüência de gestantes portadoras do HBsAg em uma comunidade brasileira - Geraldo Duarte; Marisa Márcia Mussi-Pinhata; Roberto Martinez; Cláudia Lemos; Eduardo M. Leite Figueiredo; Silvana Maria Quintana (Pan American Health Organization, 1997)
The work reported here points up the real benefits provided by neonatal immunoprophylaxis of newborns delivered by mothers who are seropositive for the hepatitis B virus surface antigen HBsAg and underscores the need to properly identify such mothers in Brazil so that immunoprophylaxis can be undertaken. To help determine levels of hepatitis B virus (HBV) infection and seropositivity for various HBV markers among pregnant women in Southeast Brazil, investigators studied 7992 pregnant women delivering at the Clinical Hospital of the University of São Paulo's Ribeirão Preto School of Medicine in Ribeirão Preto, Brazil. Seroreactivity for HBsAg was determined first by serologic screening with an enzyme-linked immunosorbent assay (ELISA) procedure in which the sera were incubated for 2 hours and then by confirmation with another ELISA in which the sera were incubated for 18 hours. Subsequently, tests for anti-HBsAg, HBeAg, anti-HBeAg, and anti-HBcAg markers were conducted using confirmed positive samples. Initial screening found 84 of the 7992 samples (1.05%, 95% CI: 0.84-1.30) to be positive for HBsAg; however, this HBsAg positivity was confirmed in only 76 (0.95%, 95% CI: 0.75-1.19). The positivity rate was significantly higher among subjects whose pregnancies terminated in miscarriage (1.84%) than among those with live births (0.83%) (chi2, Yates correction = 7.6; P = 0.005). Anamnesis was able to identify HBV risk factors in only 27.6% of the confirmed HBsAg-positive subjects or close household contacts. However, 21.3% (95% CI: 1.04-30.56) of the confirmed HBsAg-positive subjects were found positive for HBeAg, indicating a high risk of vertical transmission of the virus. These results demonstrate a need to conduct specific serologic research at term, in order to provide effective neonatal immunoprophylactic benefits. Visando aferir a tasa de reatividade sérica do HBsAg e de outros marcadores da infecção pelo VHB em parturientes, além de avaliar quais os fatores de risco, estudaram-se 7992 mulheres que tiveram ...